Evaluation of the propylene glycol association on some physical and chemical properties of mineral trioxide aggregate - Duarte, M. A. H.; Alves de Aguiar, K.; Zeferino, M. A.; Vivan, R. R.; Ordinola-Zapata, R.; Tanomaru-Filho, M. [UNESP]; Weckwerth, P. H.; Kuga, Milton Carlos [UNESP] (Wiley-Blackwell, 2012)
Duarte MAH, Alves de Aguiar K, Zeferino MA, Vivan RR, Ordinola-Zapata R, Tanomaru-Filho M, Weckwerth PH, Kuga MC. Evaluation of the propylene glycol association on some physical and chemical properties of mineral trioxide aggregate. International Endodontic Journal, 45, 565570, 2012. Abstract Aim To evaluate the influence of propylene glycol (PG) on the flowability, setting time, pH and calcium ion release of mineral trioxide aggregate (MTA). Methodology Mineral trioxide aggregate was mixed with different proportions of PG, as follows: group 1: MTA + 100% distilled water (DW); group 2: MTA + 80% DW and 20% PG; group 3: MTA + 50% DW and 50% PG; group 4: MTA + 20% DW and 80% PG; group 5: MTA + 100% PG. The ANSI/ADA No. 57 was followed for evaluating the flowability and the setting time was measured by using ASTM C266-08. For pH and calcium release analyses, 50 acrylic teeth with root-end cavities were filled with the materials (n = 10) and individually immersed in flasks containing 10 mL deionized water. After 3 h, 24 h, 72 h and 168 h, teeth were placed in new flasks and the water in which each specimen was immersed had its pH determined by a pH metre and the calcium release measured by an atomic absorption spectrophotometer with a calcium-specific hollow cathode lamp. Data were analysed by using one-way anova test for global comparison and by using Tukeys test for individual comparisons. Results The highest value of flowability was observed with MTA + 20% DW and 80% PG and the lowest values were found with MTA + 100% DW. They were significantly different compared to the other groups (P < 0.05). The presence of PG did not affect the pH and calcium release. The MTA + 100% PG favoured the highest (P < 0.05) pH and calcium release after 3 h. Increasing the PG proportion interfered (P < 0.05) with the setting time; when used at the volume of 100% setting did not occur. Conclusion The addition of PG to MTA-Angelus increased its setting time, improved flowability and increased the pH and calcium ion release during the initial post-mixing periods. The ratio of 80% DW 20% PG is recommended.
Keywords: calcium release; flowability; mineral trioxide aggregate; pH; propylene glycol; setting time